Linking anthropometric indices with components of metabolic syndrome among Nigerian adolescents - Susan J. Holdbrooke; Bamgboye M. Afolabi; Oluseye O. Onabanjo; Islamiat O. Salau; Olayinka T. Lucas (Academia Medicine)
Objective: This study aims to evaluate independent and combined association of body mass index (BMI)-for-age percentile (pctl) and waist circumference (WC) with components of metabolic syndrome (MetS) among Nigerian adolescents. Materials and methods: Cross-sectional data of biochemical and anthropometric indices were collected. Each subject was assessed for abnormal WC, elevated blood pressure (BP), diabetic fasting plasma glucose (FPG) level, and high levels of total cholesterol (T-Chol), triglyceride (TG), low-density lipoprotein-cholesterol (LDL-C), and low levels of high-density lipoprotein-cholesterol (HDL-C). Correlation and linear regression analyses were used to clarify the association between BMI-for-age pctl and WC in relation to the variables of MetS. Receiver operating characteristic curve was used to determine the diagnostic ability and optimal threshold of BMI-for-age pctl and WC for MetS and its components. The area under the curve (AUC) differences between BMI-for-age pctl and WC and components of MetS were compared. Results: Totally 624 adolescents were included in the analysis, of whom 52 (8.3%) met the criteria for MetS. Both BMI-for-age pctl and WC had equivalent ability to predict MetS with AUCs of 0.6847 (p-value < 0.0001) and 0.6479 (p-value < 0.0001) for BMI-for-age pctl and WC, respectively. Conclusions: Both BMI-for-age pctl and WC were effective screening tools to diagnose MetS. BMI-for-age pctl seemed a better predictor of MetS than WC in our study sample of predominantly Nigerian adolescents living in an urban area. Both BMI-for-age pctl and WC can be easily measured and are cost effective. Their application for predicting MetS among Nigerian adolescents has vital clinical utility.